Implementation of Canva-Based Technology Learning to Improve Student Activeness at SDIT Cendekia Purwakarta - Suharyanto Soro; Nana Herdiana Abdul Rahman; Amelia Pratiwi; Silvi Madya (Global Education Journal, 2026)
The low activity of students in elementary school is often identified by the lack of active participation, such as students who are passive in listening, reluctant to ask questions, discuss, or do class assignments. This is due to teacher-centered learning methods, abstract/boring materials, and psychological factors such as fear of mistakes and lack of confidence that reduce motivation and focus on learning. This study aims to describe the application of Canva technology-based learning in increasing student activity at SDIT Cendekia Purwakarta. The researcher uses a case study approach. Data were collected through observation, interviews, and documentation methods of learning activities. The results showed that the use of Canva-based learning media significantly increased student activity characterized by increased interaction, participation in discussions, and motivation to learn. Canva Media has proven to be an engaging and interactive learning tool. The conclusion of the study is that the application of Canva technology-based learning can be used as an innovative alternative to improve the quality of learning in elementary schools.